FOOT EXERCISE DENGAN KOMBINASI MUSIK DAPAT MENINGKATKAN NILAI ANKLE BRACHIAL INDEKS (ABI) PADA LANSIA DENGAN DIABETES MELLITUS TIPE II DI KOTA PADANG - ALFIANUR; YUREYA NITA; DESTI PUSWATI; YENI DEVITA; DINI MAULINDA (Jurnal Ners, 2022)
Diabetes mellitus is a chronic disease caused by damage to the pancreas so that it cannot produce insulin or impaired metabolism of the body so that the use of insulin produced by the pancreas cannot be effective.Complications of Diabetes Mellitus (DM) that often occur in the elderly are peripheral arterial disease (PAP). PAP can cause foot ulcers, amputation and even death. One way to detect PAP is the Ankle Brachial Index (ABI). Foot Escercise can improve blood circulation in the feet while music can help reduce pain. The purpose of this study was to determine the effect of foot exercise with a combination of music on increasing ABI in the elderly with type II diabetes. This type of research is quantitative research with the design used is Non Equivalent Control Group. Method that is Non Probability using purposive sampling technique. The results of the statistical test t-test obtained p value 0.01 <0.05. Conclusions Foot exercise with a combination of music is effective in increasing ABI in the elderly with type II diabetes. Suggestions for foot exercise with a combination of music can be applied in nursing services such as Puskesmas as an innovation program, especially in the prolanis program.